Life in the weather-world: examining an eighteenth-century 'ecological perspective'. Issue 4 (7th August 2016) - Pillatt, Toby
ABSTRACT: Within archaeology, discussions on climate are usually framed in the broad scale and long term, but by using diaries as rich sources on local environmental and landscape history, it is possible to develop archaeological insights into climate predicated on the everyday human experience of living in the landscape. This article presents a case study of two Quaker diarists, who farmed on the edge of the Lake District in north-west England during the eighteenth century. One of these diarists, Elihu Robinson, had a world view that linked social, natural and religious spheres of action with his compassionate and deeply felt faith. Arguably, this is an example of a Quaker 'ecological perspective' which contributed to an eighteenth-century environmental ethic. By thinking in terms of Tim Ingold's weather-world, it is possible to see how this perspective emerged in relation to the diarists' interactions with weather and landscape.